APPLICATION OF THE UNIFAC MODEL TO LIQUID-LIQUID EQUILIBRIA OF WATER-PROPIONIC ACID-SOLVENT TERNARIES* - Süheyla ÇEHRELİ (Pamukkale University Journal of Engineering Sciences, 2003)
The liquid-liquid equilibria of Water-Propionic Acid-Benzyl Alcohol, Water-Propionic Acid-Benzyl Acetate and Water-Propionic Acid-Dibenzyl Ether ternary systems were predicted by means of UNIFAC Model. For this purpose, multivariable Newton-Raphson convergence procedure was used. Experimental and model results were compared.